Unsung heroes in health education and promotion: How Community Health Workers contribute to hypertension management - Bush, Kim; Patrick, Carlea; Elliott, Kimberly; Morris, Michael; Tiruneh, Yordanos; McGaha, Paul (Frontiers in Public Health, 2023)
Rural communities are noted as having poor health outcomes. Northeast Texas is documented as one of the least healthy regions of the state, with a prevalence of chronic disease significantly above both state and national averages (Nehme et al., 2021). Rural areas experience barriers to care primarily due to a lack of resources, including education, health insurance, transportation, and social support. Additionally, poor health outcomes are a consequence of poor health literacy skills. Community Health Workers (CHWs) are utilized as a resource to combat these issues. This study focused on a CHW led Self-Management Blood Pressure (SMBP) program offered through the University of Texas at Tyler Health Science Center. The goal of the program was to improve management of hypertension through awareness, education, navigation, advocacy, and resource assistance. The SMBP program included structured workshops and regular follow-up with participants including connections to community resources and social support. CHWs worked closely with physicians providing bi-directional feedback on referrals and engagement of communities through outreach events. Furthermore, CHWs aided to bridge cultural or linguistic gaps between service providers and community members. Data is provided indicating this CHW-led intervention played a significant role in improving hypertension through education of how to make lifestyle changes that impact overall health and quality of life. Participants gained knowledge encouraging them to create lifelong healthy habits, coping skills, stress management, self-care, and accountability. Through this innovative approach, participants thrived in the supportive and encouraging environment led by CHWs as well as improved their blood pressure management.